Exercise-Induced Circulating Hematopoietic Stem and Progenitor Cells in Well-Trained Subjects - Kröpfl, Julia M.; Beltrami, Fernando G.; Gruber, Hans-Jürgen; Stelzer, Ingeborg; Spengler, Christina M. (Frontiers in Physiology, 2020)
It has been proposed that exercise-induced systemic oxidative stress increases circulating hematopoietic stem and progenitor cell (HPC) number in active participants, while HPC clonogenicity is reduced post-exercise. However, HPCs could be protected against exercise-induced reactive oxygen species in a trained state. Therefore, we characterized the acute exercise-induced HPC profile of well-trained participants including cell number, clonogenicity and clearance. Twenty-one healthy, well-trained participants- 12 runners, 9 cyclists; age:30.0yrs (SD4.3)- performed a strenuous acute exercise session consisting of 4 bouts of 4-min high-intensity with 3-min low-intensity in-between, which is known to elicit oxidative stress. Average power/speed of intense phases was 85% of the peak achieved in a previous incremental test. Before and 10min after exercise, CD34+/45dim cell number and clonogenicity, total oxidative (TOC) and antioxidative capacities, as well as CD31 expression on detected HPCs were investigated. TOC significantly decreased from 0.093nmol/l (SD0.059) to 0.083nmol/l (SD0.052) post-exercise (p=0.044). Although HPC proportions significantly declined below baseline (from 0.103% (SD0.037) to 0.079% (SD0.028) of mononuclear cells, p<0.0001), HPC concentrations increased post-exercise (2.10cells/µl (SD0.75) to 2.46cells/µl (SD0.98), p=0.002) without interaction between exercise modalities, while HPC clonogenicity was unaffected. Relating HPC concentrations and clonogenicity to exercise session specific (anti-) oxidative parameters, no association was found. CD31 median fluorescent intensity expression on detected HPCs was diminished post-exercise (from 1675.9 (SD661.0) to 1527.1 (SD558.9), p=0.023) and positively correlated with TOC (rrm=0.60, p=0.005). These results suggest that acute exercise-reduced oxidative stress influences HPC clearance but not mobilization in well-trained participants. Furthermore, a well-trained state protected HPCs’ clonogenicity from post-exercise decline.